Factors Influencing the Accounting Recording of Micro, Small, and Medium Enterprises in East Bolaang Mongondow Regency - Radita Rizal Mubarak; Johny Manaroinsong; Miryam P. Lonto (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2023)
This study aims to examine the factors that influence financial records in Micro, Small, and Medium Enterprises (MSMEs) in East Bolaang Mongondow Regency. This research is quantitative with a survey method. The population of this study was 3061 SMEs, with a sample size of 342, using a simple random sampling technique. The data were analyzed using linear regression. The results showed that a good understanding of accounting and perceptions of the benefits of accounting had an effect on MSME financial records, while herding behavior had no effect on MSME financial records. This research has implications for MSME actors to further strengthen relations between fellow business actors so that they can exchange experiences about the businesses they run and make good and correct financial records.